Promoviendo aprendizajes significativos en ciencias naturales, a partir de los proyectos pedagógicos productivos huerta-gallinero (2020)
This final work aims to promote significant learning in natural sciences with the 5th grade students of the educational institution Los Andes, Tierra de Hombres headquarters, through the productive educational projects of the school garden and chicken coop and at the same time the awareness of the environment they have, take advantage of it in a sustainable way so that in the future they have the ability to create their vegetable garden and / or chicken coop at home for productive purposes that will serve them in their daily lives. The conceptual delimitation of the work focuses on three axes: natural and environmental sciences, meaningful learning and productive pedagogical projects (PPPs). In the axis of natural and environmental sciences, theoretical support is based on the authors Hernández (2012), cited by Del Valle (2017); Piñango (2013), quoted by Del Valle (2017); Guhl (2012); in terms of significant learning, it is illuminated by the statements of Rodríguez (2011), Moreira (2008), Ausubel (1963, 1973) and Pozo (1989); and in relation to PPPs, Escola (1998); Tasama, Cañas, Morales, De la Torre (2013), Vasco (2013), (Forero, et al.); MEN (2010), are in the theoretical orientation of this axis. It was focused under a qualitative methodology of a descriptive nature through a didactic strategy characterized by three moments: 1-Design of a didactic learning strategy ED, 2-Implementation of the didactic strategy, 3-Evaluation of the impact of the didactic strategy with the productive pedagogical projects through a rubric, which led the students to obtain significant learning in the area of natural sciences regarding the feeding of chickens and the preparation of organic fertilizers, to actively participate in the development of the proposed activities, the construction of new concepts, hypotheses, verify results, collaborative teamwork with respect and responsibility towards the other and nature. Finally, from the implementation of the didactic strategy and the validation of the rubric, it allowed the achievement of an effective and coherent learning experience between school practices and their environment